2007
DOI: 10.1021/tx700095u
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of S-Nitrosocysteine via S- to N-Transnitrosation

Abstract: S-Nitrosothiols are thought to be important intermediates in nitric oxide signaling pathways. These compounds are unstable, in part, through their ability to donate NO. One model S-nitrosothiol, Snitrosocysteine is particularly unstable. Recently, it was proposed that this compound decomposed via intra-and intermolecular transfer of the NO group from the sulfur to the nitrogen to form Nnitrosocysteine. This primary nitrosamine is expected to rapidly rearrange to ultimately form a reactive diazonium ion interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 16 publications
4
17
1
Order By: Relevance
“…Curiously, a recent report described activation of MMP-9 by selected concentrations of SPER-NO, which appears to counter our observations, although the mechanism of activation was not addressed (28). First, only high concentrations of an exceptionally reactive S-nitrosothiol, CSNO (29), were found to weakly activate proMMP9, consistent with earlier findings (4), but the biological significance of this is questionable because biological concentrations of SNO are in the nanomolar range (30). Second, although several diverse NO donors and S-nitro-sothiols are similarly capable of inducing S-nitrosylation within a peptide that represents the Cys-containing prodomain region of proMMP-9, the fact that most of these agents cannot activate proMMP-9 would suggest that S-nitrosylation may not be responsible for MMP-9 activation by CSNO or by other RNS (4,9).…”
Section: Discussioncontrasting
confidence: 85%
“…Curiously, a recent report described activation of MMP-9 by selected concentrations of SPER-NO, which appears to counter our observations, although the mechanism of activation was not addressed (28). First, only high concentrations of an exceptionally reactive S-nitrosothiol, CSNO (29), were found to weakly activate proMMP9, consistent with earlier findings (4), but the biological significance of this is questionable because biological concentrations of SNO are in the nanomolar range (30). Second, although several diverse NO donors and S-nitro-sothiols are similarly capable of inducing S-nitrosylation within a peptide that represents the Cys-containing prodomain region of proMMP-9, the fact that most of these agents cannot activate proMMP-9 would suggest that S-nitrosylation may not be responsible for MMP-9 activation by CSNO or by other RNS (4,9).…”
Section: Discussioncontrasting
confidence: 85%
“…1B). Similar exposure to CSNO resulted in a more transient loss of TER during the first 2–3 hrs, consistent with its limited chemical stability [25], and did not significantly enhance permeability to FITC-Dextran over 24 hrs (Fig. 1).…”
Section: Resultssupporting
confidence: 56%
“…The irradiated solutions were then analyzed using HPLC. It was found that disulfide was the major product in argon saturated solutions, in agreement with earlier reports [5][6][7][8][9]. Meanwhile, in aerated solutions, nitrite was also formed along with disulfide.…”
Section: Resultssupporting
confidence: 90%
“…S-Nitrosothiols (RSNO) are generally believed as the bio reservoir for nitric oxide (NO) in a biological system [1] and hence their various ways of decomposition are very relevant [2][3][4][5][6][7]. The bond dissociation energy for S-N bond is between 20 and 32 kcal mol −1 [8,9].…”
Section: Introductionmentioning
confidence: 99%